Quality of Life in Non‐Melanoma Skin Cancer—The Skin Cancer Quality of Life (SCQoL) Questionnaire. Issue 12 (14th November 2013) - Vinding, Gabrielle Randskov; Christensen, Karl Bang; Esmann, Solveig; Olesen, Anne Braae; Jemec, Gregor B. E.
<x xml:space="preserve">Abstract</x> Background Disease‐specific quality of life (QoL) questionnaires are increasingly used to provide patient‐reported out‐come measures in both malignant and non‐malignant disease. Objective To create, validate and test the psychometrics of the Skin Cancer Quality of Life (SCQoL), which was designed to measure health‐related QoL in patients with non‐melanoma skin cancer affecting any area and undergoing any therapy. Methods and Materials The SCQoL was developed in a stepwise approach. Three pilot studies (testing content and face validity) and psychometric testing (scale structure, reliability, domains and known‐groups validity, concurrent and convergent validity) were conducted. Rasch analyses were performed on the final questionnaire. Results The initial 10‐item questionnaire was reduced to 9 items following interviews and inter‐item correlations. The nine item scale was confirmed by Item Response Theory (IRT) and internal consistency. Differential Item Functioning (DIF) was found for a single item, but the effect was small. Conclusion The final 9‐item SCQoL is unidimensional and consists of 3 domains covering function, emotions and control. Furthermore there is one single global item. The total score range from 0 to 27. Higher score denote a greater impairment of the QoL.